PARIWISATA TERPADU DI KAWASAN STONE GARDEN DESA GUNUNG MASIGIT, KECAMATAN CIPATAT, KABUPATEN BANDUNG - Ade Perdana Putra; Tio Buana Putra; Andrio Saputra; Yusuf Baihaqi; Wely Yelvia Sartika; Fella Melifa; Suci Allara Putri; Rika Reskika; Suci Rahmadani; Amrin Sobirin; Yurni Suasti; Sri Mariya; Murni Sulastri (JURNAL BUANA, 2020)
This study was designed to describe and manage integrated tourism areas in the Masigit Village, Cipatat District, West Bandung Regency. The method used in this study is a survey method using primary and secondary data. The results of this study produce a description of the debate in the tourist area such as opposing the road to the location which is still a dirt road and bumpy and when it rains it becomes very muddy. Then in the development of the amount of money from three attractions in Indiana Camp Monthly income can reach Rp. 2,000,000-Rp. 20,000,000. The percentage of the number of visits also increased, Winus visits in 2014 amounted to 93.27% increased in 2018 to 98.35% while foreign tourists in 2014 amounted to 0.065% increased to 1.65% in 2018.